VD_FINDINFO Décision / 2014 / 110 vom 6. Februar 2014 - VD Tribunal cantonal (2014)
DIFFAMATION, BONNE FOI SUBJECTIVE, NON-LIEU, DROIT D'ÊTRE ENTENDU | 14 CP, 173 ch. 1 CP, 173 ch. 2 CP, 173 ch. 3 CP, 318 CPP (CH), 319 al. 1 CPP (CH)